Analisis Komitmen Organisasi Melalui Faktor Quality Of Work Life (Studi Kasus Fakultas Ekonomi dan Manajemen Institut Pertanian Bogor) (Jurnal Manajemen dan Organisasi, 2016)
The purpose of this study were (1) to analyze the Quality of work life (QWL)condition in FEM, (2) to analyze the relationship between organizational commitment with the Quality of work life (QWL) in FEM, (3) to analyze Quality of Work Life (QWL) factors was the most influential on organizational commitment in the FEM. Type of data used in this study are primary and secondary data. Census method was the sampling method was used in this research. Processing and data analysis in this study was using SPSS software, Minitab, and Microsoft Excel. Results from this study indicated that the WQL has been pretty good in the FEM IPB. The relationship between quality of work life with organizational commitment has been good with a Spearman correlation showed a positive relationship, significant and rather strong. Quality of work life factors that most influence on organizational commitment is the integration of work environment factors with coefficients of a high standard compared to other factors that QWL.